2021
DOI: 10.3390/nu13082790
|View full text |Cite
|
Sign up to set email alerts
|

Influence of COVID-19 Pandemic Restrictions on College Students’ Dietary Quality and Experience of the Food Environment

Abstract: The COVID-19 pandemic restrictions sent college students online and off campus, potentially reducing access to healthy food. The objective of this cross-sectional, internet-based study was to use qualitative and quantitative survey methods to evaluate whether COVID-19 pandemic restrictions in Texas, USA affected college students’ ability to buy food, how/what they shopped for, how they prepared food, what they ate, how they felt about eating, and overall dietary quality (assessed using Healthy Eating Index [HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 51 publications
2
32
0
Order By: Relevance
“…Of these, nearly half were conducted in the United States of America (USA) (n = 4) ( Adams et al, 2020 , 2021 ; Hammons and Robart, 2021 ; Silva et al, 2021 ), followed by two in Latin America (Brazil, Mexico) ( Gonzalez-Alejo et al, 2020 ; Horta et al, 2021 ), and one each in Africa (Zimbabe) ( Murendo et al, 2021 ), Asia (China) ( Ahmed et al, 2020 ), and the Pacific Islands (Samoa) ( Emiliata et al, 2020 ). The majority of studies reported changes in external food environments, including the natural, built ( Ahmed et al, 2020 ; FAO, 2020 ) and digital ( Horta et al, 2021 ), home food environments ( Adams et al, 2020 , 2021 ; Hammons and Robart, 2021 ), and household and individual-level food acquisition practices ( Emiliata et al, 2020 ; Murendo et al, 2021 ; Silva et al, 2021 ) since the onset of the pandemic, with differences and similarities observed between level of country development, stringency of pandemic-related mitigation strategies, and socio-economic status. The one multi-country study that has been conducted interviewed urban food system stakeholders such as provincial government officers ( FAO, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, nearly half were conducted in the United States of America (USA) (n = 4) ( Adams et al, 2020 , 2021 ; Hammons and Robart, 2021 ; Silva et al, 2021 ), followed by two in Latin America (Brazil, Mexico) ( Gonzalez-Alejo et al, 2020 ; Horta et al, 2021 ), and one each in Africa (Zimbabe) ( Murendo et al, 2021 ), Asia (China) ( Ahmed et al, 2020 ), and the Pacific Islands (Samoa) ( Emiliata et al, 2020 ). The majority of studies reported changes in external food environments, including the natural, built ( Ahmed et al, 2020 ; FAO, 2020 ) and digital ( Horta et al, 2021 ), home food environments ( Adams et al, 2020 , 2021 ; Hammons and Robart, 2021 ), and household and individual-level food acquisition practices ( Emiliata et al, 2020 ; Murendo et al, 2021 ; Silva et al, 2021 ) since the onset of the pandemic, with differences and similarities observed between level of country development, stringency of pandemic-related mitigation strategies, and socio-economic status. The one multi-country study that has been conducted interviewed urban food system stakeholders such as provincial government officers ( FAO, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The one multi-country study that has been conducted interviewed urban food system stakeholders such as provincial government officers ( FAO, 2020 ). From the above studies, only three sought to understand the lived experiences of food environment changes during the pandemic using qualitative methodologies ( Emiliata et al, 2020 ; Hammons and Robart, 2021 ; Silva et al, 2021 ). No study to date has assessed the impact of Covid-19-related mitigation strategies on food environments at the consumer level across multiple countries or contexts during the early months of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…In the past two years since the COVID-19 pandemic started, college students have faced financial hardships that might increase their food insecurity risk and need for food assistance [ 26 , 27 ]. Thus, it is expected that students with food insecurity are willing to take advantage of the free food resources available to them, specifically on-campus resources such as food pantries.…”
Section: Discussionmentioning
confidence: 99%
“…Students, in particular, are affected by the COVID-19 pandemic through the spread of several unhealthy behaviors, such as sedentary activities, poor dietary habits, and reduced sleep quality, which in turn affect their stress levels and depression [21,22]. During the current pandemic, restrictions and lockdown procedures contributed to inadequate food choices, resulting in a poorer quality of diet for students [23].…”
Section: Introductionmentioning
confidence: 99%